THE MODERN VIEW OF THE PATHOGENESIS AND LABORATORY DIAGNOSTICS OF ULCERATIVE COLITIS (LITERATURE REVIEW) - V. I. Sovalkin; G. R. Bikbavova; Yu. A. Emel’yanova (Архивъ внутренней медицины, 2017)
The basic theory of the pathogenesis of inflammatory bowel disease (IBD) is currently considered a violation of immune activation and immune response against its own antigens to the intestinal flora in genetically predisposed individuals. “The gold standard” diagnosis of UC is colonoscopy with biopsy morphological study. Due to the invasiveness, complexity in the preparing and conducting, the high cost of endoscopy there is a need in the application of laboratory biomarkers UC, with which you can select a group of persons subject to an in-depth examination of the instrumental. Thereview highlights the modern view of the pathogenesis of the disease, the ability to use a variety of laboratory biomarkers in the diagnosis of UC, for monitoring the effectiveness of the therapy, as predictors of severe course of UC, therapeutic response prediction and early detection of recurrence